Effectiveness of ‘Instagram’ on the Patronage of Commercial Organisations - Omolara Oluwabusayo Akin-Odukoya; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
Instagram, a popular social media platform with over a billion active users, has become a powerful tool for commercial organizations. Its visual-centric format, engagement features, and advertising capabilities provide businesses with unique opportunities to attract and retain customers. This analysis explores the effectiveness of Instagram in driving patronage for commercial organizations. Instagram has proven to be an effective platform for driving patronage for commercial organizations. Its visual-centric approach, robust engagement tools, and targeted advertising capabilities enable businesses to increase brand awareness, engage customers, and drive sales. However, success on Instagram requires a strategic approach, continuous effort, and adaptability to platform changes and audience preferences. By leveraging Instagram’s unique features and maintaining authenticity, businesses can significantly enhance their patronage and overall success. This study employed Uses and Gratification Theory and the survey method was used in the study. The population of this study consists of students of Caleb University. As such, the total number of students in Caleb University is 3000. The sample size selected for this study is Six hundred (600) and purposive sampling technique was adopted to select Six hundred (600) sample size. The findings of the study show students use Instagram for several purposes. It was also observed that the students assess the Instagram network in various ways and with different gadgets. The study concludes that the students pay a moderate level of attention to Instagram as this indicated that there was less addiction level by the students to the platform.